The debate between a man and his soul : a masterpiece of ancient Egyptian literature - Allen, James P., 1945- (Culture and History of the Ancient Near East, 2011)
This book is a new study of the ancient Egyptian poem known in English as The Man Who Was Tired of Life or The Dialogue of a Man and His Ba (or Soul ). The composition is universally regarded as one of the masterpieces of ancient Egyptian literature. It is also one of the most difficult and continually debated, as well as being the subject of more than one hundred books and articles. The present study offers new readings and translations, along with an analysis of the text's grammar and versification, and a complete philological apparatus.